KNOX1 genes regulate lignin deposition and composition in monocots and dicots - Townsley, Brad T.; Sinha, Neelima R.; Kang, Julie (Frontiers in Plant Science, 2013)
Plant secondary cell walls are deposited mostly in vascular tissues such as xylem vessels, tracheids, and fibers. These cell walls are composed of a complex matrix of compounds including cellulose, hemicellulose, and lignin. Lignin functions primarily to maintain the structural and mechanical integrity of both the transport vessel and the entire plant itself. Since lignin has been identified as a major source of biomass for biofuels, regulation of secondary cell wall biosynthesis has been a topic of much recent investigation. Biosynthesis and patterning of lignin involves many developmental and environmental cues including evolutionarily conserved transcriptional regulatory modules and hormonal signals. Here, we investigate the role of the class I Knotted1-like-homeobox (KNOX) genes and gibberellic acid in the lignin biosynthetic pathway in a representative monocot and a representative eudicot. Knotted1 overexpressing mutant plants showed a reduction in lignin content in both maize and tobacco. Expression of four key lignin biosynthesis genes was analyzed and revealed that KNOX1 genes regulate at least two steps in the lignin biosynthesis pathway. The negative regulation of lignin both in a monocot and a eudicot by the maize Kn1 gene suggests that lignin biosynthesis may be preserved across large phylogenetic distances. The evolutionary implications of regulation of lignification across divergent species are discussed.